Review of The Method of Valuation of The SDR-Proposed Extension of The Valuation Of The SDR Basket and Modification of The Date Of Effect of A New Basket. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2021)
On March 5, 2021, the IMF's Executive Board approved an extension of the current Special Drawing Right (SDR) valuation basket by ten months from September 30, 2021 to July 31, 2022. The IMF normally reviews the composition and valuation of the SDR basket every five years. The extension effectively resets the five-yearly cycle of SDR valuation reviews, with the next review to be completed by mid-2022 and the new basket becoming effective on August 1, 2022. The ten-month extension contributes to the Fund's ongoing efforts to prioritize work during the COVID-19 crisis and allows for a more suitable effectiveness date of the new basket, which does not coincide with some major markets being closed. The approved extension, as well as effectiveness date of a new basket, is intended to facilitate the continued smooth functioning of SDR-related operations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; SDR Allocation Workstream; SDR Interest Basket; SDR User; SDR Valuation Review; China, People's Republic of